Farm visit Z again (Karakul Circulations: Colonial Economies and the Un_Making of Disciplinary Knowledges in Germany and Namibia, 2021)
908 JPEG files documenting participant observation on a farm near Mariental
Keywords: Karakul sheep; Sheep-shearing; Postcolonialism; South Africa; Agriculture; Colonisation; Namibia; Swakara; Karakul Circulations; Colonial Economies; Karakul Farming; Germany; Colonial South-West Africa; German Colonialism; Karakul Sheep Industry